Biosynthesis of C12 Fatty Alcohols by Whole Cell Biotransformation of C12 Derivatives Using Escherichia coli Two-cell Systems Expressing CAR and ADH - 차태용; 육용; 박현아; 윤혜정; 전우영; 안정오; 최권영 (Biotechnology and Bioprocess Engineering, 2021)
In this study, the conversions of 1-dodecanoic, ω-hydroxydodecanoic acid and α,ω-dodecanedioic acid using whole cell biotransformation of Escherichia coli BW25113ΔfadD expressing CAR and ADH enzymes were demonstrated. First 13 CAR enzymes were examined for 1-dodecanoic acid reduction, and CAR encoded by mab4714 from Mycobacterium abscessus showed the highest conversion of 53.1% in single cells of heterologous CAR and endogenous ADH. For a better conversion, the host cells were engineered to simultaneously express Yarrowia lipolytica ADH2 with the GroES/EL-DnaK/J/E chaperone in a single host system. In addition, two-cell system using two strains of E. coli expressing CAR-Sfp and ADHGroES/ EL-DnaK/J/E was also investigated. In results, additional ADH expression was not effective in a single host system, whereas two cell system significantly increased α,ω-dodecanedioic acid conversion by total 71.3%; α,ω- dodecanediol (68.2%) and ω-hydroxydodecanoic acid (3.1%), respectively. Interestingly, the MAB4714 CAR enzyme could converted ω-hydroxydodecanoic acid into α,ω- dodecanediol up to 97.2% conversion in 17 h (12.4 mg/L/h). Finally, structural understanding of the higher activity against ω-hydroxydodecanoic was understood by docking simulations which suggested hydrogen-bonding interactions between ω-hydroxyl group and polar residues such as Gln434 and Thr285 were holding the substrate tightly with more stable positioning in the active site.
Keywords: alcohol dehydrogenase; carboxylic acid reductase; two cell reactions; reductive metabolites; whole cell biotransformation